The emergence of academic pediatric acute and urgent care fellowships: entrustable professional activities - Haroon Shaukat; Deena Berkowitz; Ioannis Koutroulis; Emily Willner (Medical Education Online)
Objectives The Accreditation Council for Graduate Medical Education (ACGME) defined 6 core competencies (medical knowledge, patient care, practice-based learning and improvement, systems-based practice, interpersonal and communication skills, and professionalism) to be used as a framework for outcomes-based assessment. Concurrent to the development of specialty-specific competencies and milestones, the concept of entrustable professional activities (EPAs) were introduced. EPAs describe what a learner can do at each of the 5 levels of entrustment. There are four pediatric acute and urgent and urgent care (PAC) fellowships to date, however, no curricular consensus exists. This article seeks to develop a set of nationally agreed-upon PAC-specific EPAs to be used by emerging fellowships.Methods Multi-step iterative qualitative study using a web-based survey was used for EPA development and validity. A modified-Delphi panel, comprised of pediatric educators from multiple institutions, participated in four rounds to reach consensus (≥80%). EPAs were ranked using a 5 point-Likert scale, then from most important to least important in series, and finally individually as yes/no for each EPAs inclusion.Results Survey response rate was 83% (19/23). Six of the 7 EPAs were deemed on average to be high priority or essential. There was clear consensus on four EPAs and less agreement amongst the other three. Ultimately, 3 of the 7 EPAs reached consensus for inclusion, with agreement ranging from 84% to 100%.Conclusion(s) PAC-specific EPAs focusing on clinical excellence, procedural competence, and high-quality care were all deemed essential components for PAC fellowships. Delineation of these EPAs will be critical to guide development of fellowship curricula.